A parenting education tool using videos and debates for parents with pre-school children - Ailincai, Rodica; Weil-Barais, Annick (Swiss Journal of Educational Research, 2018)
In the first part of the paper, we present a set of parenting education tools designed for parents with children aged 3 to 7 years, without any special needs. The educational tools we are interested in are the ones that are supported by videos and/or the ones that focus on exchanges/discussions between parents. Our presentation of these tools is based on a general framework which aims to objectify intervention tools used in education and training: the IMTE framework (Intentions, Mediation, Tools, and Effects). In the second part, we present a model that we conceived and elaborated from parenting education practices during experiments carried out in a science museum context in a detailed way. In the conclusion section, as well as the characteristics and the use of video recordings in parenting education tools, we draw the readers attention to the role of normativity in such educational tools.